2011
DOI: 10.4161/rna.8.1.13767
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of intracellular RNA pharmacokinetics: Implications for RNA-based immunotherapeutics

Abstract: RNAs with optimized properties are increasingly investigated as a tool to deliver the genetic information of complete antigens into professional antigen-presenting dendritic cells for HLA haplotype-independent antigen-specific vaccination against cancer. As the dose of the antigen and duration of its presentation are critical factors for generating strong and sustained antigen-specific immune responses, improvement of the immunobioavailability of RNA-based vaccines has been a recurrent subject of research. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 101 publications
(121 reference statements)
1
25
0
Order By: Relevance
“…It has been suggested that the immunobioavailability of antigen mRNA is a critical success-limiting factor in view of cancer therapy (34). First, we showed high antigen expression when mRNA was delivered in Ca 2þ -containing HBSS or the clinically applied 0.8 RL, confirming the Ca 2þ dependency for efficient uptake of mRNA (29).…”
Section: Discussionsupporting
confidence: 55%
“…It has been suggested that the immunobioavailability of antigen mRNA is a critical success-limiting factor in view of cancer therapy (34). First, we showed high antigen expression when mRNA was delivered in Ca 2þ -containing HBSS or the clinically applied 0.8 RL, confirming the Ca 2þ dependency for efficient uptake of mRNA (29).…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, Holtkamp et al ., have shown that 2 copies of 3′ UTR from β-globin result in increased protein levels and mRNA stability only in immature dendritic cells, whereas in mature dendritic cells, no effect could be observed18. Cell specificity of UTRs when combined with mRNA has been also observed for other cells and tissues and has been discussed in the recent reviews4142.…”
Section: Discussionmentioning
confidence: 93%
“…In vitro-synthesized mRNAs encoding tumor antigens can be used to elicit an immune response in dendritic cells, and vaccination with such mRNAs has already entered clinical testing for the treatment of cancer (Weide et al 2008;Diken et al 2011). The use of a cleavage-resistant cap increases mRNA stability and translational efficiency of exogenous mRNA in mice and enhances priming and expansion of naive antigen-specific T-cells (Kuhn et al 2010(Kuhn et al , 2011. In Saccharomyces pombe, oligouridylation of poly(A)-containing mRNA by the noncanonical poly(A) polymerase Cid1 has been demonstrated Norbury 2008, 2009).…”
Section: Blocking the 39 End Stabilizes Luc-slmentioning
confidence: 99%